Assertiveness Training Strategy for Preventing Sexual Violence Among Students at MTs Wahid Hasyim Blitar Regency - Umi Aisyah; Muhammad Sholihuddin Zuhdi; Nurul Hidayat (Al Huwiyah: Journal of Woman and Children Studies, 2026)
Sexual violence against adolescents is a serious issue requiring systematic prevention through strengthening personal competencies. This study evaluates assertiveness training as a preventive strategy among adolescents at MTs Wahid Hasyim, Pikatan Village. A mixed-methods embedded design was used with quantitative data as primary and qualitative data as supporting data. Thirty students were selected purposively. Pre- and post-test knowledge assessments were used to collect quantitative data. Qualitative data were collected through behavioral observations during intervention sessions. The intervention included lectures, discussions, simulations, and role-plays to build assertiveness skills. Results showed scores increased from 56.5 to 84.0, a 48.67% improvement. Observations showed improved self-confidence, boundary-setting, and assertive techniques such as I-statements and the broken record. Both data sources indicate assertiveness training reduces vulnerability by strengthening boundary communication skills. The study recommends integration into school counseling services with structured institutional prevention policies.